2022
DOI: 10.1002/batt.202200328
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Formulations and Scalable Processes for Producing Sulfidic Solid‐State Batteries

Abstract: Solid-state batteries possess the potential to combine increased energy densities, high voltages, as well as safe operation and therefore are considered the future technology for electrical energy storage. In particular, sulfides as solid electrolyte are promising candidates due to their high ionic conductivities and the possibility of a scalable production. This review aims to demonstrate ways to manufacture suspension-based sulfidic solid-state batteries both on a laboratory scale and on an industrial level,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 143 publications
(465 reference statements)
0
39
0
Order By: Relevance
“…Mixing routine: It was shown that the sequence of mixing seems to have a small but significant influence on the performance of composite cathodes. Achieving a high mixing efficiency by applying different methods, such as extrusion processes, seems to be a promising way forward to increase the achievable specific capacities [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mixing routine: It was shown that the sequence of mixing seems to have a small but significant influence on the performance of composite cathodes. Achieving a high mixing efficiency by applying different methods, such as extrusion processes, seems to be a promising way forward to increase the achievable specific capacities [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…All‐solid‐state batteries are receiving a lot of development attention recently, with significant progress being made in solid electrolyte materials discovery and their processability [26–29] . Figure 2 presents the room‐temperature ionic conductivity band diagram comparing various solid‐state electrolyte materials reported to date; the data for the plot were obtained from previous publications [26,30–36] .…”
Section: Figurementioning
confidence: 99%
“…All-solid-state batteries are receiving a lot of development attention recently, with significant progress being made in solid electrolyte materials discovery and their processability. [26][27][28][29] Figure 2 presents the room-temperature ionic conductivity band diagram comparing various solid-state electrolyte materials reported to date; the data for the plot were obtained from previous publications. [26,[30][31][32][33][34][35][36] Most of the solid-state electrolytes presented in Figure 2 have some stability issues either at lower or higher potentials and may require SEEI (solid-electrolyte/ electrode interphase) films; that is, either SEAI or SECI films at particle level and/or electrode level for electrochemical stability.…”
mentioning
confidence: 99%
“…However, industrial-scale production requires the establishment of larger scalable equipment. [1,14,15] 3. Dispersion: In addition to carbon black networks, the formation of ionic conductivity pathways is required.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] Analogous issues also exist for the dispersion of powders in solvents: Planetary centrifugal mixers are generally used, [18][19][20][21] which have neither been investigated with regard to the process-engineering influence of various process parameters, nor are available on a large scale (maximum product quantity 14.5 kg). [14] Alternatives from the field of conventional lithium-ion batteries that meet these requirements are planetary mixers, kneaders and twinscrew extruders. [22][23][24] Based on this and taking into account the identified challenges, this publication aims to establish and improve an industrially scalable dispersion process under inert gas atmosphere.…”
Section: Introductionmentioning
confidence: 99%